Faktor yang Berhubungan Dengan Pemanfaatan Pelayanan Posyandu Lansia di Wilayah Kerja Puskesmas Antara Kota Makassar - Aisyah Nur Rahma icha; Amran Razak; Suci Rahmadani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The coverage of health services for the elderly at the Antara Public Health Center is 62.1%. Posyandu for the elderly is an effort made to increase health coverage for the elderly, the elderly who utilize Posyandu are 558 people out of 1152 elderly. This study aims to determine the factors related to the use of Posyandu for the elderly in the work area of ​​the Antara City Health Center in Makassar. The type of research used is quantitative research design, analytical descriptive study, with a cross sectional approach. The sample is set at 90 samples with stratified random sampling technique. The instrument used is a structured questionnaire. Data analysis using Chi-square test. The results showed that age (p=0.093), education (p=0.000), knowledge (p=0.000), family support (p=0.000), distance (p=0.000), and perception of pain (p=0.000) has a relationship with the use of Posyandu for the elderly in the work area of ​​the Makassar City Health Center. There was no relationship between gender (p=0.147) and occupation (p=0.117) on the utilization of the Posyandu for the elderly in the work area of ​​the Antara City Health Center in Makassar. most of the variables studied in this study showed a significant relationship. It is hoped that health workers/posyandu cadres will further increase the socialization/counseling activities given to the elderly regarding the importance of conducting health checks at the posyandu for the elderly.